Illegality of Sexual Violence against Women during Armed Conflicts - Miebaka Nabiebu (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract. Sexual violence against women during conflict situations has been a common phenomenon throughout history. It has been regarded as a strategy to terrorise and gain control over civilian society. The atrocities of the Bosnian War, the Sierra Leone Civil War, and the Rwandan Genocide are some events that attest to women's vulnerability in warfare. The Nuremberg Charters conceived and established the concept of international crimes and individual liability for violations of international law. Thus, the general acceptance of rape and sexual violence as “normal” or “trophies of war” is no longer tolerated with the growing consciousness of gender equality and human rights. Recently, International Humanitarian Law (IHL) has recognised the illegality of rape and sexual violence during armed conflict. Given the foregoing, the main goal of this study is to comprehend how IHL safeguards women during times of armed conflict. This work discussed the topics of sexual violence as a war crime and human rights. The Special Court for Sierra Leone (SCSL) and the International Criminal Tribunal for Rwanda (ICTR) were also covered in this piece. Finally, this investigation examined the institutional reactions to several case studies of sexual assault offenders. This work argues that the International Criminal Tribunal for Yugoslavia (ICTY), the International Criminal Tribunal for Rwanda (ICTR), and the Special Court for Sierra Leone (SCSL) played a vital role in the prosecution of perpetrators of sexual violence. This work suggests that crimes of sexual violence should not be included in amnesty provisions. Keywords: Sexual violence, Women, Armed Conflicts, International Humanitarian Law